1996
DOI: 10.1016/s0304-3959(96)03215-0
|View full text |Cite
|
Sign up to set email alerts
|

Pain in ambulatory AIDS patients. I: Pain characteristics and medical correlates

Abstract: The characteristics and impact of pain were evaluated in a prospective cross-sectional survey of 438 ambulatory AIDS patients recruited from health care facilities in New York City. More than 60% of the patients reported 'frequent or persistent pain' during the 2 wks preceding the study. Patients with pain reported an average of 2.5 different pains. On the 0-10 numerical scale of the Brief Pain Inventory (BPI), mean pain intensity 'on average' was 5.4 (SD = 2.2; range = 0-10), and mean pain 'at its worst' was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
174
4
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(196 citation statements)
references
References 15 publications
15
174
4
3
Order By: Relevance
“…The present results are consistent with prior research indicating increased pain report among IDUs with HIV (Fantoni et al 1997;Martin et al 1999;Vogl et al 1999;Del Borgo et al 2001). However, our findings are inconsistent with reports that found no differences in pain report in HIV+ IDUs and non-IDUs (Breitbart et al 1996a;Breitbart et al 1997). One possibility is that overall, the Breitbart samples had more advanced disease-i.e., roughly 70% met criteria for AIDS, whereas only 36.3% of the HCSUS sample met criteria for AIDS.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present results are consistent with prior research indicating increased pain report among IDUs with HIV (Fantoni et al 1997;Martin et al 1999;Vogl et al 1999;Del Borgo et al 2001). However, our findings are inconsistent with reports that found no differences in pain report in HIV+ IDUs and non-IDUs (Breitbart et al 1996a;Breitbart et al 1997). One possibility is that overall, the Breitbart samples had more advanced disease-i.e., roughly 70% met criteria for AIDS, whereas only 36.3% of the HCSUS sample met criteria for AIDS.…”
Section: Discussioncontrasting
confidence: 99%
“…It was a latent variable indicated by 2 items: 1) The respondent's clinical category based upon AIDS diagnoses: 1 = asymptomatic/PGL (persistent generalized lymphadenopathy); 2 = symptomatic; 3 = AIDS indicator condition; and 2) Whether the respondent had wasting syndrome (1 = no; 2 = yes). CD4 count was not included because prior work indicated no relationship between CD4 and pain in HIV+ individuals (Breitbart et al 1996a;). …”
Section: Questionnaire Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with prior work demonstrating that HIV+ patients who are injection drug users (IDUs) report more pain than non-IDUs (Fantoni et al 1997;Martin et al 1999;Vogl et al 1999;Del Borgo et al 2001), although null findings have also been reported (Breitbart et al 1996a;Breitbart et al 1997). Previously, we found that patients with problematic drug use history experienced greater HIV/AIDS illness burden, which in turn predicted greater pain (Tsao et al 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Several other studies in treatment-seeking, chronic pain populations have reported a similar pattern of results (Edwards et al 2005;Green et al 2003;McCracken et al 2001;Edwards et al, 1999;Greenwald, 1991). Additional evidence indicates ethnic differences in the severity of pain associated with several medical conditions, including AIDS (Breitbart et al 1996), glaucoma (Sherwood et al 1998), and arthritis (Creamer et al 1999). …”
Section: Introductionmentioning
confidence: 99%